Semiannual Variation of Microparticle Concentration in Snow Drift at Mizuho Station, Antarctica in 1977 - Fujii, Yoshiyuki (1981)
P(論文) The concentration of microparticle in snow drift collected at Mizuho Station, Antarctica in 1977 shows a semiannual variation with two maxima in January and February of the summer season and in May to July of the winter seasons, and two minima in March and August to October of the intermediate seasons. The semiannual cycle is probably ascribed to (1) the dilution of microparticle transported from the lower latitudes by fallen snow in the intermediate seasons and (2) the semiannual cycle of stratospheric aerosol concentration and precipitation over Antarctica. departmental bulletin paper